Nighty night! - McNaughton, Colin (London Walker, 2008)
"No-no-no-no-no-no-no!" said Littlesaurus. "Yes," said Daddysaurus. "It's time for bed." Littlesaurus doesn't want to go to bed and can think of a million reasons to stay up. This is a bedtime story, filled with prehistoric humour, that can help even the most exasperated parents get their toddler to bed, and have them chuckling as they do so.